Prehospital tourniquet use in penetrating extremity trauma: Decreased blood transfusions and limb complications. Issue 1 (January 2019) - Smith, Alison A.; Ochoa, Joana E.; Wong, Sunnie; Beatty, Sydney; Elder, Jeffrey; Guidry, Chrissy; McGrew, Patrick; McGinness, Clifton; Duchesne, Juan; Schroll, Rebecca
Abstract : BACKGROUND: Despite increasing popularity of prehospital tourniquet use in civilians, few studies have evaluated the efficacy and safety of tourniquet use. Furthermore, previous studies in civilian populations have focused on blunt trauma patients. The objective of this study was to determine if prehospital tourniquet use in patients with major penetrating trauma is associated with differences in outcomes compared to a matched control group. METHODS: An 8-year retrospective analysis of adult patients with penetrating major extremity trauma amenable to tourniquet use (major vascular trauma, traumatic amputation and near-amputation) was performed at a Level I trauma center. Patients with prehospital tourniquet placement (TQ) were identified and compared to a matched group of patients without tourniquets (N-TQ). Univariate analysis was used to compare outcomes in the groups. RESULTS: A total of 204 patients were matched with 127 (62.3%) in the prehospital TQ group. No differences in patient demographics or injury severity existed between the two groups. Average time from tourniquet application to arrival in the emergency department (ED) was 22.5 ± 1.3 minutes. Patients in the TQ group had higher average systolic blood pressure on arrival in the ED (120 ± 2 vs. 112 ± 2, p = 0.003). The TQ group required less total PRBCs (2.0 ± 0.1 vs. 9.3 ± 0.6, p < 0.001) and FFP (1.4 ± 0.08 vs. 6.2 ± 0.4, p < 0.001). Tourniquets were not associated with nerve palsy ( p = 0.330) or secondary infection ( p = 0.43). Fasciotomy was significantly higher in the N-TQ group (12.6% vs. 31.4%, p < 0.0001) as was limb amputation (0.8% vs. 9.1%, p = 0.005). CONCLUSION: This study demonstrated that prehospital tourniquets could be safely used to control bleeding in major extremity penetrating trauma with no increased risk of major complications. Prehospital tourniquet use was also associated with increased systolic blood pressure on arrival to the ED, decreased blood product utilization and decreased incidence of limb related complications, which may lead to improved long-term outcomes and increased survival in trauma patients. LEVEL OF EVIDENCE: Therapeutic, level IV.